Method for preparing iron-carbon-based catalyst from coal liquefaction residue raffinate
By mixing the coal directly liquefied residue, biomass and bonded coal in a specific proportion and performing procedure heating treatment, an iron-carbon-based catalyst was prepared, which solved the problem that the coal liquefied residue was not effectively utilized and the catalyst activity stability was difficult to maintain, and the effect of improving the yield of light components of coal pyrolysis tar and extending the service life of the catalyst was achieved.
Patent Information
- Application Number
- CN202311432008.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-10-31
- Publication Date
- 2025-05-02
AI Technical Summary
In the prior art, the liquefied coal residue residues cannot be effectively utilized, and the activity and stability of the catalysts are difficult to maintain during the catalytic pyrolysis of coal, and are prone to inactivation due to carbon deposits and coking.
Iron-carbon-based catalyst is prepared by mixing the coal directly liquefied residue, biomass and bonded coal in a specific proportion and subjecting to procedural heating treatment. This method not only effectively utilizes the coal liquefied residue raffinate, but also improves the activity and stability of the catalyst.
The iron-carbon-based catalyst significantly improves the yield of light components in tar during coal pyrolysis and biomass co-pyrolysis, extends the service life of the catalyst, reduces production costs, and promotes resource utilization and environmental protection.
Smart Images

Figure FT_1 
Figure FT_2
Abstract
Description
Technical Field
[0001] The invention belongs to the field of coal chemical industry and catalyst preparation, and specifically relates to a method for preparing an iron-carbon based catalyst from coal liquefaction residue extract Background Art
[0002] As the core of coal classification and quality utilization, medium and low temperature pyrolysis technology can obtain coal gas, liquid tar and solid semi-coke products. Semi-coke is used as gasification / calcium carbide raw material, and pyrolysis gas is used for synthesizing chemicals. Coal tar contains a large amount of aromatic hydrocarbons and phenolic compounds, which can be used as high value-added chemical raw materials. However, the heavy components (boiling point above 360℃) in coal tar produced by medium and low temperature pyrolysis process are o C) has a high content, and low-rank coal is easily pulverized. Fine particles are carried out of the reactor by pyrolysis oil and gas, which can easily block the pipeline and affect the stable operation of the process. Under current technical conditions, the main methods to increase the content of light components in coal pyrolysis tar are: pyrolysis in a hydrogen-rich atmosphere such as hydrogen and methane, co-pyrolysis with high hydrogen-to-carbon ratio materials such as biomass, and catalytic modification of coal pyrolysis products. Among them, pyrolysis in a hydrogen-rich atmosphere has problems such as high pyrolysis cost, high hydrogen preparation cost, and gases such as hydrogen and methane themselves have high calorific value and are expensive. In contrast, the coal pyrolysis catalytic modification process has a good development prospect. The direct catalytic pyrolysis process of coal is to directly add a catalyst to participate in the pyrolysis reaction of coal during the pyrolysis process, which can effectively increase the content of light components in coal pyrolysis tar.
[0003] Coal liquefaction is one of the ways to achieve clean and efficient conversion of coal. However, direct coal liquefaction technology produces a large amount of solid residue while producing liquefied oil, which accounts for about 20%-30% of the mass of the raw coal. At present, the separation of liquefied asphalt from coal liquefaction residues has been achieved in industry through extraction, but the disposal of coal liquefaction residues is still an industrial problem. For existing technologies, coal liquefaction residues still lack effective utilization.
[0004] At present, in the catalytic pyrolysis utilization of coal, there are still many problems with catalysts, and their activity and stability are often challenged. During the catalytic pyrolysis of coal, due to the complex temperature distribution inside the reactor, it is easy to cause carbon deposition and coking to accumulate on the catalyst surface, affecting the activity of the catalyst. Carbon deposition will block the pore structure of the catalyst, causing the reaction rate to slow down or even stop. In addition, impurities, mineral components and high temperature conditions in coal will cause the catalyst to deactivate and deactivate, reduce its service life, and reduce the reaction efficiency. The present invention provides a method for preparing an iron-carbon-based catalyst, and the catalytic activity and stability of the prepared catalyst are better than most catalysts with similar effects at present, and the iron-carbon-based catalyst uses coal liquefaction residue extract, biomass, and caking coal as the main raw materials, and its production cost is low, and the coal liquefaction residue extract is effectively utilized, which can play a positive role in resource utilization and environmental protection. The catalyst can significantly improve the yield of light components in coal pyrolysis tar alone and coal and biomass co-pyrolysis tar. Summary of the invention
[0005] The purpose of the present invention is to provide a method for preparing an iron-carbon based catalyst from coal liquefaction residue extract. The present invention not only effectively utilizes the coal direct liquefaction residue extract, but also provides a method for preparing an iron-carbon based catalyst with good catalytic activity and good stability.
[0006] The basic principle of the present invention is as follows: the residue extract of direct coal liquefaction contains abundant waste iron-containing catalysts, but the residue extract of direct coal liquefaction contains very little organic matter and active components and lacks carbon carriers. Biomass, as an easily available renewable energy source, contains abundant organic matter and minerals, which can supplement carbon and minerals for the reaction. The residue of direct coal liquefaction itself has a certain adhesiveness, but the residue extract of direct coal liquefaction after extraction does not produce colloids due to its extremely low organic content. In order to make the catalyst easier to shape, it is necessary to add appropriate adhesive coal. The higher adhesive index of adhesive coal can play a role in bonding the catalyst to shape it, and at the same time can improve the mechanical strength of the catalyst after shaping.
[0007] The invention provides a method for preparing an iron-carbon based catalyst. Firstly, coal direct liquefaction residue extract powder, biomass powder and caking coal powder are mixed, and then the temperature is increased to 200-400°C at a heating rate of 0.5-5°C / min and kept warm for 20-60 min, and then the temperature is increased to 600-1200°C at a heating rate of 3-10°C / min and kept warm for 30-120 min.
[0008] Specifically, the steps of the preparation method of an iron-carbon based catalyst provided by the present invention are as follows: (1) Dry, crush, screen and dry the coal liquefaction residue. The particle size of the coal liquefaction residue should be between 0.05 mm and 0.4 mm.
[0009] (2) The biomass is dried, crushed, and sieved for later use. The biomass has an alkaline earth metal and alkali metal content of more than 3000 μg / g, including but not limited to cotton stalks, algae, elm bark, etc. Since the density of biomass and coal liquefaction residue is quite different, in order to ensure the mixing effect after stirring, the particle size of biomass should be 0.3-1.2 times that of coal liquefaction residue.
[0010] (3) The caking coal is crushed, sieved, and dried for later use. The particle size distribution of the caking coal should be as similar as possible to the particle size distribution of the coal liquefaction residue.
[0011] (4) The coal liquefaction residue extract powder in step (1) is fully mixed with the biomass powder and the sticky coal powder in steps (2) and (3). The mass ratio of the coal direct liquefaction residue extract powder to the biomass powder is between 1:0.1 and 1:5, the mass ratio of the coal direct liquefaction residue extract powder to the sticky coal powder is between 1:0.1 and 1:5, the coal direct liquefaction residue extract powder accounts for 30%-70% of the total mass, and the alkali metal contained in the biomass in the mixed powder accounts for 0.3% to 10% of the total mass.
[0012] (5) Add the mixed powder in step (4) into the reactor and perform programmed heating. Raise the temperature to 200-400°C at a heating rate of 0.5-5°C / min and keep it at that temperature for 20-60 min, then raise the temperature to 600-1200°C at a heating rate of 3-10°C / min and keep it at that temperature for 30-120 min.
[0013] (6) The solid particles after the reaction are allowed to cool naturally to obtain a catalyst.
[0014] Preferably, the particle size of the coal liquefaction residue extract should be between 0.1 mm and 1 mm.
[0015] Preferably, the alkaline earth metal and alkali metal content of the biomass is between 5000-10000 μg / g.
[0016] Preferably, the mass ratio of the coal direct liquefaction residue powder to the biomass powder is between 1:0.4 and 1:1.
[0017] Preferably, the mass ratio of the coal direct liquefaction residue extract powder to the caking coal powder is between 1:0.4 and 1:1.
[0018] Preferably, the powder of the coal direct liquefaction residue extract accounts for between 40% and 60% of the total mass, and the alkali metal contained in the biomass in the mixed powder accounts for between 1% and 5% of the total mass.
[0019] Preferably, the programmed temperature rise process should first be heated to 250-350°C at a heating rate of 1-3°C / min and kept at that temperature for 30-60 min, and then heated to 500-800°C at a heating rate of 3-5°C / min and kept at that temperature for 50-100 min.
[0020] The activation mechanism of the waste iron-containing catalyst in the coal liquefaction residue extract in the present invention is as follows: the main form of iron in the coal liquefaction residue extract is iron sulfide. Under high temperature conditions, the ionic bond between the iron ion and the sulfur ion in the iron sulfide is broken, and the iron ion is oxidized to form iron oxide. The carbon material carrier has a strong adsorption effect on iron oxide, and the activated active iron will be adsorbed in the pores of the carbon carrier, and the iron oxide combines with the carbon carrier to form Fe2O3 / C. In the present invention, at 200-400 ° C, the unstable components in the biomass and the caking coal are decomposed to generate substances such as CO2, CO, and small molecular organic matter. When the temperature is raised to 600-1200 ° C, the biomass and the caking coal are pyrolyzed to generate heavy oil, small molecular organic matter, etc. In this process, the minerals contained in the biomass can play a certain catalytic role, the iron sulfide of the coal liquefaction residue extract is decomposed, and substances such as CO2 react with sulfur ions to take sulfur ions out of the system, and the active iron ions are adsorbed by the carbon carrier to form an iron-carbon based catalyst. During the catalyst activation process, the pores of the carbon carrier change, the specific surface area increases, and the particle size of the iron oxide particles becomes smaller and more evenly distributed.
[0021] Beneficial effects of the present invention: (1) The residue extract from direct coal liquefaction is difficult to utilize under existing technical conditions. The present invention can effectively utilize the residue extract from direct coal liquefaction.
[0022] (2) The present invention provides a method for preparing an iron-carbon based catalyst, which can play a role in multiple aspects, especially in the catalytic reforming process of coal pyrolysis, and can significantly increase the yield of light components in the tar produced by the pyrolysis of coal alone and the tar produced by the co-pyrolysis of coal and biomass. BRIEF DESCRIPTION OF THE DRAWINGS Figure 1 It is a summary diagram of the catalyst preparation method of each embodiment; Figure 2 Results of coal pyrolysis experiment and coal and biomass co-pyrolysis experiment DETAILED DESCRIPTION
[0023] In order to better describe the content and advantages of the present invention, the present invention is described in detail below in conjunction with specific embodiments, but the present invention is not limited to the following embodiments. On the contrary, the purpose of providing these embodiments is to make the understanding of the disclosure of the present invention more thorough and comprehensive.
[0024] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as those commonly understood by those skilled in the art of the present invention. The terms used in the specification of the present invention herein are only for the purpose of describing specific embodiments and are not intended to limit the present invention.
[0025] Example 1
[0026] In this embodiment, experiments were conducted using coal liquefaction residues from a certain place in Xinjiang, cotton stalks, and fat coal as raw materials.
[0027] (1) Pretreatment: Place the coal liquefaction residue, cotton stalks, and fat coal in a dry, ventilated, and sunlight-free place at room temperature to dry for later use. After drying, crush the coal liquefaction residue into powder with a particle size of 0.18-0.25 mm, crush the cotton stalks into powder with a particle size of 0.10-0.15 mm, and crush the fat coal into powder with a particle size of 0.18-0.25 mm for later use. Take 5 g of coal direct liquefaction residue extraction residue powder, 2.5 g of cotton stalk powder, and 2.5 g of fat coal powder for later use.
[0028] (2) High temperature treatment: The coal direct liquefaction residue extraction residue powder, cotton stalk powder and fat coal powder were fully mixed and placed in a muffle furnace for high temperature treatment. The temperature was increased to 300 °C at a heating rate of 1 °C / min and kept at this temperature for 30 min. Then, the temperature was increased to 700 °C at a heating rate of 5 °C / min and kept at this temperature for 60 min.
[0029] (3) The product obtained in (2) is cooled to room temperature to obtain an iron-carbon based catalyst.
[0030] Example 2
[0031] In this embodiment, the experiment was conducted using coal liquefaction residues and cotton stalks from a certain place in Xinjiang as raw materials.
[0032] (1) Pretreatment: Place the coal liquefaction residue extract and cotton stalks at room temperature, dry, ventilated, and not exposed to direct sunlight to dry for later use. After drying, crush the coal liquefaction residue extract into powder with a particle size between 0.18-0.25 mm, and crush the cotton stalks into powder with a particle size between 0.10-0.15 mm for later use. Take 5 g of coal direct liquefaction residue extract residue powder and 5 g of cotton stalk powder for later use.
[0033] (2) High temperature treatment: The coal direct liquefaction residue extraction residue powder, cotton stalk powder and fat coal powder were fully mixed and placed in a muffle furnace for high temperature treatment. The temperature was increased to 300 °C at a heating rate of 1 °C / min and kept at this temperature for 30 min. Then, the temperature was increased to 700 °C at a heating rate of 5 °C / min and kept at this temperature for 60 min.
[0034] (3) The product obtained in (2) is cooled to room temperature to obtain an iron-carbon based catalyst.
[0035] Example 3
[0036] In this embodiment, experiments were conducted using coal liquefaction residues and fat coal from a certain place in Xinjiang as raw materials.
[0037] (1) Pretreatment: Place the coal liquefaction residue extract and fat coal in a dry, ventilated place at room temperature and not exposed to direct sunlight to dry for later use. After drying, crush the coal liquefaction residue extract into powder with a particle size between 0.18-0.25 mm, and crush the fat coal into powder with a particle size between 0.18-0.25 mm for later use. Take 5 g of coal direct liquefaction residue extract residue powder and 5 g of fat coal powder for later use.
[0038] (2) High temperature treatment: The coal direct liquefaction residue extraction residue powder, cotton stalk powder and fat coal powder were fully mixed and placed in a muffle furnace for high temperature treatment. The temperature was increased to 300 °C at a heating rate of 1 °C / min and kept at this temperature for 30 min. Then, the temperature was increased to 700 °C at a heating rate of 5 °C / min and kept at this temperature for 60 min.
[0039] (3) The product obtained in (2) is cooled to room temperature to obtain an iron-carbon based catalyst.
[0040] Example 4
[0041] In this embodiment, cotton stalks and fat coal were used as raw materials for experiments.
[0042] (1) Pretreatment: Place cotton stalks and fat coal in a dry, ventilated place at room temperature and not exposed to direct sunlight to dry for later use. Grind the cotton stalks into powder with a particle size between 0.10-0.15 mm, and grind the fat coal into powder with a particle size between 0.18-0.25 mm for later use. Take 5 g of cotton stalk powder and 5 g of fat coal powder for later use.
[0043] (2) High temperature treatment: The coal direct liquefaction residue extraction residue powder, cotton stalk powder and fat coal powder were fully mixed and placed in a muffle furnace for high temperature treatment. The temperature was increased to 300 °C at a heating rate of 1 °C / min and kept at this temperature for 30 min. Then, the temperature was increased to 700 °C at a heating rate of 5 °C / min and kept at this temperature for 60 min.
[0044] (3) The product obtained in (2) is cooled to room temperature to obtain an iron-carbon based catalyst.
[0045] Example 5
[0046] In this embodiment, experiments were conducted using coal liquefaction residues from a certain place in Xinjiang, cotton stalks, and fat coal as raw materials.
[0047] (1) Pretreatment: Place the coal liquefaction residue, cotton stalks, and fat coal in a dry, ventilated, and sunlight-free place at room temperature to dry for later use. After drying, crush the coal liquefaction residue into powder with a particle size of 0.18-0.25 mm, crush the cotton stalks into powder with a particle size of 0.15-0.10 mm, and crush the fat coal into powder with a particle size of 0.18-0.25 mm for later use. Take 5 g of coal direct liquefaction residue extraction residue powder, 2.5 g of cotton stalk powder, and 2.5 g of fat coal powder for later use.
[0048] (2) High temperature treatment: The coal direct liquefaction residue extraction residue powder, cotton stalk powder and fat coal powder were fully mixed and placed in a muffle furnace for high temperature treatment. The temperature was increased to 500 °C at a heating rate of 10 °C / min and kept at this temperature for 60 min. Then, the temperature was increased to 800 °C at a heating rate of 1 °C / min and kept at this temperature for 30 min.
[0049] (3) The product obtained in (2) is cooled to room temperature to obtain an iron-carbon based catalyst.
[0050] Example 6
[0051] In this embodiment, experiments were conducted using coal liquefaction residues from a certain place in Xinjiang, cotton stalks, and fat coal as raw materials.
[0052] (1) Pretreatment: Place the coal liquefaction residue, cotton stalks, and fat coal in a dry, ventilated, and sunlight-free place at room temperature to dry for later use. After drying, crush the coal liquefaction residue into powder with a particle size of 0.18-0.25 mm, crush the cotton stalks into powder with a particle size of 0.15-0.10 mm, and crush the fat coal into powder with a particle size of 0.18-0.25 mm for later use. Take 5 g of coal direct liquefaction residue extraction residue powder, 2.5 g of cotton stalk powder, and 2.5 g of fat coal powder for later use.
[0053] (2) High temperature treatment: The coal direct liquefaction residue extraction residue powder, cotton stalk powder and fat coal powder were fully mixed and placed in a muffle furnace for high temperature treatment. The temperature was increased to 200 °C at a heating rate of 10 °C / min and kept at this temperature for 30 min. Then, the temperature was increased to 700 °C at a heating rate of 15 °C / min and kept at this temperature for 60 min.
[0054] (3) The product obtained in (2) is cooled to room temperature to obtain an iron-carbon based catalyst.
[0055] Comparing the tar yield and the proportion of light components in the tar without and with the catalyst, it can be seen that the catalyst can significantly increase the tar yield of coal pyrolysis and biomass co-pyrolysis while significantly increasing the content of light components in the tar, especially the light component content, which significantly improves the quality of the tar. The catalyst has extremely poor mechanical properties, is in the form of black particles, has fewer pores inside the particles, has a small specific surface area, and has significantly weaker catalytic performance than Example 1.
[0056] The catalyst preparation methods of each embodiment are summarized in the attached Figure 1
[0057] To verify the catalytic effect of the catalyst, we conducted coal pyrolysis experiments and coal and biomass co-pyrolysis experiments without and with the addition of catalyst. The experimental results are summarized in the attached Figure 2 .
Claims
1. A method for preparing an iron-carbon based catalyst, characterized in that The method comprises the following steps: (1) Drying, crushing, screening and drying the coal liquefaction residue, biomass and caking coal respectively to obtain coal liquefaction residue powder with a certain particle size, biomass powder with a certain particle size and caking coal powder with a certain particle size; (2) Take a certain amount of coal liquefaction residue powder, a certain amount of biomass powder, and a certain amount of caking coal powder, mix them thoroughly, and spread them evenly in a crucible; (3) placing the crucible containing the mixed powder in step (2) into a muffle furnace for high temperature treatment, first heating the temperature to a certain temperature at a certain heating rate and maintaining the temperature for a certain time, the temperature should be slightly higher than the temperature at which the caking coal is pyrolyzed to produce colloids, then heating the temperature to a certain temperature at a relatively fast heating rate, the temperature should be higher than the temperature at which the iron sulfide in the coal liquefaction residue extract is decomposed, and maintaining the temperature for a period of time to ensure that the iron sulfide is completely decomposed and the biomass and the caking coal are completely pyrolyzed; (4) After the reaction is completed, the crucible is taken out and allowed to cool naturally to obtain an iron-carbon based catalyst; (5) The catalytic performance of the catalyst can be significantly improved after activation.
2. The method according to claim 1, characterized in that The particle size of the coal liquefaction residue extract in step (1) should be between 0.05 and 4 mm.
3. The method according to claim 1, characterized in that: The alkaline earth metal and alkali metal content of biomass is above 3000 μg / g, including but not limited to cotton stalks, algae, elm bark, etc.
4. The method according to claim 1, characterized in that: The particle size distribution of the caking coal should be as similar as possible to that of the coal liquefaction residue. Since the density of the biomass, caking coal and coal liquefaction residue is quite different, in order to ensure the mixing effect after stirring, the particle size of the biomass should be appropriately smaller than that of the coal liquefaction residue and the caking coal. Specifically, the particle size of the biomass should be 0.3-1.2 times that of the particle size of the coal liquefaction residue.
5. The method according to claim 1, characterized in that The programmed temperature rise process in step (7) should comply with the following requirements: first, heat to 200-400 °C at a heating rate of 0.5-5 °C / min and keep warm for 20-60 min, then heat to 600-900 °C at a heating rate of 3-10 °C / min and keep warm for 30-120 min.
6. The method according to claim 1, characterized in that The catalyst activation method in step (5) includes but is not limited to activation using water vapor, carbon dioxide, etc.
7. The method according to claim 1, characterized in that include: The solid residue after extraction of coal liquefaction residue is used for waste utilization; the required organic matter and minerals are supplemented by biomass; and the catalyst is formed by utilizing the high content of adhesive coal colloid.
8. The method according to claim 1, characterized in that The mass ratio of the coal direct liquefaction residue extract powder to the biomass powder is between 1:0.1 and 1:5, and the mass ratio of the coal direct liquefaction residue extract powder to the caking coal powder is between 1:0.1 and 1:
5.
9. The method according to claim 1, characterized in that: The powder of the residue extracted from the direct coal liquefaction residue accounts for between 30% and 70% of the total mass.
10. The method according to claim 1, characterized in that The alkali metal contained in the biomass in the mixed powder accounts for between 0.3% and 10% of the total mass.